Enthesitis in psoriatic arthritis (Part 1): pathophysiology - Araujo, Elizabeth G.; Schett, Georg (Rheumatology, 2020)
Enthesitis is a key manifestation of PsA and current knowledge supports the concept that it may be among the primary events in the development of this disease, as well as other forms of SpA. Patients with PsA seem to have a different threshold to mechanical stress, which may be genetically determined. Hence patients with psoriatic disease respond pathologically with inflammation after being exposed to physiological mechanical stress. Activation of pro-inflammatory mediators such as IL-17 and TNF-α as well as the influx of innate immune cells are key events in the development of enthesitis in PsA. Chronic entheseal inflammation is accompanied by new bone formation, leading to bony spurs in peripheral (entheseophytes) and axial (syndesmophytes) structures. This article reviews the current knowledge on the mechanisms involved in the development of enthesitis in patients with PsA.
CRIS-Team Scopus Importer:2020-03-27
Keywords: entheseophyte; enthesitis; interleukin 17; interleukin 23; psoriatic arthritis